Preparation method and application of silicon-oxygen-carbon negative electrode material

Through top-down mechanical ball milling method and high-temperature carbonization process, silicon oxygen carbon anode material with small particle size and excellent coating effect was prepared, which solved the problem of volume expansion and poor conductivity of silicon-based anode material during charging and discharging, significantly improved the electrochemical performance of lithium-ion batteries and reduced production costs.

CN119812273APending Publication Date: 2025-04-11SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510005457.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The silicon-based negative electrode material expands volume during charging and discharging, has poor conductivity, low Coulomb efficiency for the first time, poor circulation performance, and easy cracking of the solid electrolyte interface. The existing manufacturing methods are costly and complex, so they are not suitable for large-scale production.

Method used

The top-down mechanical ball milling method is used to perform mechanical ball milling by silicon oxide and zirconia balls, and the particle size of silicon oxide is controlled, and a mixture of anhydrous glucose and melamine is added for uniform coating, and then carbonized at high temperature to obtain a silicon oxide carbon negative electrode material with excellent carbon coating effect.

Benefits of technology

It effectively alleviates the volume expansion of silicon, improves the conductivity and electrochemical stability of the material, significantly improves the specific capacity, circulation and rate performance of the negative electrode material of lithium-ion battery, and simplifies the process, reduces costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812273A_ABST
    Figure CN119812273A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a silicon-oxygen-carbon negative electrode material, and relates to the technical field of lithium ion battery negative electrode materials. The method comprises the following steps: ball-milling a coated carbonized material, screening, calcining at high temperature and the like. The invention also provides application of the silicon-oxygen-carbon negative electrode material prepared by the preparation method in preparation of a lithium ion battery. The raw materials comprise silicon monoxide, a coating material and a negative electrode mixed material, wherein the coating material is a mixed material of melamine and anhydrous dextrose. The preparation method comprises the following steps: directly and uniformly mixing and dispersing silicon monoxide powder and a coating material in a mechanical ball milling manner, screening, and calcining at a high temperature to obtain the silicon-oxygen-carbon negative electrode material of the lithium ion battery, which is uniformly coated with carbon. The optimal carbon coating effect in mechanical grinding and mixing is achieved by adjusting the composition and proportion of the silicon monoxide-coating material, various conditions of mechanical ball milling and the like, the coating efficiency is high, and the process is simple. The obtained silicon-oxygen-carbon negative electrode material has the advantages of excellent lithium ion deintercalation capability, high reversible capacity, good rate capability, stable long-term cycle performance and low cost, and is beneficial to mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silicon-oxygen-carbon negative electrode materials, and in particular relates to a preparation method of a silicon-oxygen-carbon negative electrode material and an application thereof. Background Art

[0002] In recent years, with the rapid development of new energy vehicles and energy storage battery technology, lithium-ion batteries have attracted extensive attention and research from researchers due to their high operating voltage, large specific capacity, long cycle life, no memory effect, low self-discharge rate, environmental protection and safety. Currently, commercial graphite negative electrode materials are close to their theoretical specific capacity (372mAh / g), which is difficult to meet people's extensive needs. Therefore, it is urgent to develop lithium-ion batteries with higher energy density and safety.

[0003] The development of high-performance silicon-oxygen-carbon anode materials is crucial to improving the energy density of lithium-ion batteries. Silicon-based materials have a high theoretical specific capacity (4200mAh g -1 ), lower lithiation voltage (<0.5V vs Li + / Li) and its abundant crustal reserves have attracted widespread attention, but silicon-based materials still have some outstanding problems, which have greatly hindered their commercial application. The volume change of silicon during the charge and discharge process is as high as 300%, which leads to the pulverization of electrode materials and reduces the cycle performance of the battery. Secondly, the electronic conductivity is low and the electrical conductivity is poor, which will affect the charge and discharge performance and rate performance of the battery. In addition, the first coulomb efficiency (ICE) of the silicon-based negative electrode is low, and there will be more lithium ion loss during the first charge and discharge process. The interface is unstable. During the charge and discharge process of the silicon-based negative electrode, the solid electrolyte interface (SEI) on the electrode surface is easy to break, thereby affecting the battery cycle performance. In view of the volume expansion and poor cycle life, the more suitable method at present is to use the carbon coating technology of nano-silicon to solve it. Carbon-coated nano-silicon is a structure with nano-silicon as raw material and a carbon layer on the surface. The carbon layer can effectively protect the silicon surface, thereby avoiding direct contact between the electrode and the electrolyte and inhibiting the excessive growth of the SEI film. At the same time, the carbon shell has strong mechanical stability and can effectively alleviate the volume expansion problem of silicon itself. In addition, the particle size of silicon also plays a key role in the electrochemical performance of the battery. The larger the particle size, the lower the preparation cost, but the cycle performance is often worse. Therefore, accurate control of silicon particle size is particularly important for good coating of carbon materials. Therefore, how to more effectively alleviate the volume expansion of silicon and obtain silicon-based negative electrode materials with higher specific capacity and long cycle life is a technical hotspot that needs to be solved in the current lithium-ion battery field.

[0004] There are two main mainstream technical routes for carbon coating, including traditional grinding and vapor deposition (CVD). Due to the preparation process problems, the carbon coating effect of the traditional physical grinding method is often worse than that of the vapor deposition method. However, the vapor deposition method is temporarily not widely used due to its poor process repeatability, high processing cost and inability to be mass-produced. The present invention improves the traditional grinding process and uses a top-down method to perform ball milling in two steps to obtain a silicon-oxygen-carbon negative electrode material with a small particle size and excellent coating effect. This method is simple in process, low in cost and suitable for large-scale production. After high-temperature calcination, a lithium-ion battery negative electrode material with higher reversible capacity, cycle and rate performance is obtained. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defects of initial coulombic efficiency, cycle performance, conductivity, and easy rupture of the solid electrolyte interface caused by volume expansion and poor conductivity of silicon-based negative electrode materials during charging and discharging, as well as the shortcomings of existing manufacturing methods such as high cost, complex process, and difficulty in large-scale promotion and application.

[0006] The present invention solves the above technical problems by the following technical means:

[0007] A method for preparing a silicon oxygen carbon negative electrode material comprises the following steps:

[0008] (1) Using silicon oxide as a silicon source and anhydrous glucose as a carbon source, a certain amount of silicon oxide is put into a ball mill, and mechanically ball milled with zirconium oxide balls in a certain ratio, so that the particle size of silicon oxide is controlled within a specific range, wherein the ball-to-material ratio of zirconium oxide balls to silicon oxide is (1-10):1;

[0009] (2) adding a certain ratio of anhydrous glucose and melamine to continue mechanical ball milling so that the carbon source is evenly coated on the surface of the silicon source, then taking out the prepared mixture from the ball mill, and sieving a sample with a suitable particle size with a test sieve, wherein the mass ratio of silicon dioxide, anhydrous glucose and melamine is (1-10): (1-10): 1;

[0010] (3) placing the mixture within a specific particle size range sieved out in step (2) into a horizontal crucible furnace, and carbonizing it by high-temperature pyrolysis under the protection of an inert gas to remove excess oxygen atoms in the material, thereby obtaining the silicon-oxygen-carbon negative electrode material.

[0011] Preferably, in the step (1), the mechanical ball milling time of silicon dioxide and zirconium oxide balls is 1-10 hours, the mechanical ball milling time after adding the mixture of anhydrous glucose and melamine is 1-10 hours, and the mechanical ball milling speed is 100-300 r / min.

[0012] Preferably, in step (1), the particle size of the silicon-oxygen-carbon mixture powder obtained by ball milling is 0.05-150 um.

[0013] Preferably, in step (2), the inspection sieve mesh size is 50-500 mesh, and the particle size of the sieved sample is 0.5-50 um.

[0014] Preferably, in step (3), the heating rate during high-temperature pyrolysis is 0.5-10°C / min, the temperature is heated to 400-1000°C, and the insulation time is 1-15h.

[0015] Preferably, in step (3), the inert gas is at least one of helium, nitrogen and argon.

[0016] Preferably, in step (3), the particle size of the obtained silicon oxygen carbon negative electrode material is 0.05-50 um.

[0017] A method for preparing a silicon-oxygen-carbon negative electrode material and application of the prepared silicon-oxygen-carbon negative electrode material in preparing lithium-ion batteries.

[0018] The electrolyte of the lithium-ion battery is any one of the following solutions: LiPF6 dissolved in ethylene carbonate (EC) and (2) methyl carbonate (DMC), LiPF6 dissolved in ethylene carbonate (EC) and (2) ethyl carbonate (DEC), or LiPF6 dissolved in ethylene carbonate (EC), (2) ethyl carbonate (DEC) and (2) methyl carbonate (DMC).

[0019] Using the silicon oxygen carbon negative electrode material prepared by the above method, the LiPF6 concentration of the lithium ion battery electrolyte required for assembling button batteries is 0.5-1.5 mol / L.

[0020] The electrochemical performance of the prepared silicon oxygen carbon negative electrode material is tested by button cells. The metal lithium sheet used in the laboratory can provide an excess of lithium source, has few impurities and is larger than the electrode to be tested. Generally, the lithium sheet can be purchased directly from relevant enterprises or suppliers, and disassembled and used in a glove box under the protection of an inert atmosphere. The purity of the lithium sheet used is required to be no less than 99.9%. When used to prepare button half-cells, the diameter is often 15-15.8mm (corresponding to the CR2032 button cell with a 12mm electrode size), the thickness is 0.5-0.8mm, the surface is flat, silvery white, and there is no oil spot, perforation, or tearing. The type of diaphragm needs to be selected according to the experimental requirements. It is generally an insulating film with nanopores. After absorbing the electrolyte, it allows bidirectional ion transmission. Generally, a single-layer or multi-layer commercial polyethylene or polypropylene diaphragm is selected and made into a regular-sized circle using a punching machine. The size must be larger than the metal lithium sheet and the electrode to be tested to isolate the positive and negative electrodes. It is usually the same as the inner diameter of the button battery shell (for example, the diameter of the diaphragm used for CR2032 batteries is 15.5-16.5mm). Industrial polypropylene membranes of Celgard2400 or Celgard2500 are often used in laboratories. When assembling button batteries, the electrolyte options include ordinary electrolytes, electrolytes containing one or more additives, etc., which are usually excessive. For example, the amount of electrolyte used in button batteries CR2032 is generally 100-150μL.

[0021] Compared with the prior art, the present invention is beneficial in that:

[0022] 1. The present invention adopts a simple method to prepare silicon-oxygen-carbon negative electrode materials. Through a top-down mechanical ball milling method, silicon oxide is first pretreated to control the particle size within a suitable range; then a mixture of anhydrous glucose and melamine is added for uniform coating. The present invention achieves a good carbon coating effect by controlling the particle size of silicon oxide, the composition ratio of raw materials and ball milling conditions, effectively alleviating the volume change of silicon during the cycle, thereby improving the conductivity and electrochemical stability of the material.

[0023] 2. The silicon oxygen carbon negative electrode material prepared by the present invention is applied to lithium ion batteries, which has made significant progress in improving the specific capacity, cycle and rate performance of lithium ion battery negative electrode materials. More importantly, it proposes a method with simple process, environmental protection, low cost and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image (SEM) of the silicon oxygen carbon negative electrode material provided in Example 1 of the present invention.

[0025] Figure 2 This is the first charge and discharge capacity-voltage curve of the silicon oxygen carbon negative electrode material provided in Example 1 of the present invention.

[0026] Figure 3 This is a long cycle curve of the silicon oxygen carbon negative electrode material provided in Example 1 of the present invention at a current density of 1 A / g. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a silicon oxygen carbon negative electrode material, comprising the following steps:

[0028] (1) Using silicon oxide as a silicon source and anhydrous glucose as a carbon source, a certain amount of silicon oxide is put into a ball mill, and mechanically ball milled with zirconium oxide balls in a certain ratio, so that the particle size of silicon oxide is controlled within a specific range, wherein the ball-to-material ratio of zirconium oxide balls to silicon oxide is (1-10):1;

[0029] (2) adding a certain ratio of anhydrous glucose and melamine to continue mechanical ball milling so that the carbon source is evenly coated on the surface of the silicon source, then taking out the prepared mixture from the ball mill, and sieving a sample with a suitable particle size with a test sieve, wherein the mass ratio of silicon dioxide, anhydrous glucose and melamine is (1-10): (1-10): 1;

[0030] (3) placing the mixture within a specific particle size range sieved out in step (2) into a horizontal crucible furnace, and carbonizing it by high-temperature pyrolysis under the protection of an inert gas to remove excess oxygen atoms in the material, thereby obtaining the silicon-oxygen-carbon negative electrode material.

[0031] In step (1), the mechanical ball milling time of silicon dioxide and zirconium oxide balls is 1-10 hours, the mechanical ball milling time after adding the mixture of anhydrous glucose and melamine is 1-10 hours, the mechanical ball milling speed is 100-300r / min, and the particle size of the silicon oxygen carbon mixture powder obtained by ball milling is 0.05-150um; in step (2), the inspection sieve mesh number is 50-500 mesh, and the particle size of the sieved sample is 0.5-50um; in step (3), the heating rate during high-temperature pyrolysis is 0.5-10℃ / min, heated to 400-1000℃, and the insulation time is 1-15h, the inert gas is at least one of helium, nitrogen, and argon, and the particle size of the obtained silicon oxygen carbon negative electrode material is 0.05-50um.

[0032] The accompanying drawings are only used for illustrative purposes; for those skilled in the art, some common knowledge and prior art may be omitted; in order to better explain the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0033] Example 1

[0034] A method for preparing a silicon oxygen carbon negative electrode material comprises the following steps:

[0035] (1) Weigh 80g of silicon dioxide and 800g of zirconium oxide balls on an electronic balance, and put the weighed samples and zirconium oxide balls into a clean ball mill; place the ball mill in a planetary ball mill, rotate at 200r / min, and perform ball milling for 8h in both forward and reverse directions; weigh 10g of anhydrous glucose and 10g of melamine on an electronic balance, and put them into the above ball mill. Mix the samples in the jar to ensure full contact, and continue ball milling for 4h in the same procedure;

[0036] (2) sieving the mixed powder obtained in step (1) through a 400-mesh test sieve to obtain a powder sample with a smaller particle size;

[0037] (3) The sample obtained in step (2) was placed in a horizontal crucible furnace and heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 3 hours. Finally, the silicon-oxygen-carbon negative electrode material Si@C-1 was prepared.

[0038] Silicon oxygen carbon negative electrode material is used to make lithium ion battery negative electrode material, and the battery is subjected to constant current charge and discharge test.

[0039] from Figure 2 From the first charge and discharge curve of the silicon-oxygen-carbon negative electrode material Si@C-1, it can be seen that its initial discharge specific capacity is 2903 mAh / g and the first coulombic efficiency is 70.59%.

[0040] from Figure 3 From the long cycle curve of the silicon-oxygen-carbon negative electrode material Si@C-1 at a current density of 1A / g, it can be seen that after 100 cycles, the reversible specific capacity is still as high as 1656mAh / g, indicating that the material has very excellent long cycle performance.

[0041] Example 2

[0042] This embodiment uses 400g of zirconium oxide balls, and other matters not mentioned are consistent with those in Example 1, and finally the silicon-oxygen-carbon negative electrode material Si@C-2 is prepared.

[0043] Example 3

[0044] This embodiment uses 560g of zirconium oxide balls, and other matters not mentioned are consistent with those in Example 1, and finally the silicon oxygen carbon negative electrode material Si@C-3 is prepared.

[0045] Example 4

[0046] In this embodiment, the ball milling time of silicon dioxide and zirconium oxide balls in step (1) is 6 hours, and then the ball milling time of adding anhydrous glucose and melamine is 6 hours. Other matters not mentioned are consistent with Example 1, and finally the silicon oxygen carbon negative electrode material Si@C-4 is prepared.

[0047] Example 5

[0048] In this embodiment, the ball milling time of silicon dioxide and zirconium oxide balls in step (1) is 4 hours, and then the ball milling time of adding anhydrous glucose and melamine is 8 hours. Other matters not mentioned are consistent with Example 1, and finally the silicon oxygen carbon negative electrode material Si@C-5 is prepared.

[0049] Example 6

[0050] The final heating temperature in step (3) of this embodiment is 800° C., and other matters not mentioned are consistent with those in Example 1, and finally the silicon-oxygen-carbon negative electrode material Si@C-5 is prepared.

[0051] Example 7

[0052] The final heating temperature in step (3) of this embodiment is 1000° C., and other matters not mentioned are consistent with those in Example 1, and finally the silicon oxygen carbon negative electrode material Si@C-5 is prepared.

[0053] The electrochemical performance of the silicon oxygen carbon negative electrode material obtained was tested using a CR2032 button battery. The negative electrode material was used as the active material, sodium alginate was used as the binder, and conductive carbon black was added. According to the ratio of active material: conductive carbon black: sodium alginate = 7:2:1, an appropriate amount of deionized water was added to the mortar, and the negative electrode slurry was prepared after grinding and dispersing evenly. Then the slurry was evenly coated on the copper foil with a scraper and placed in an oven to dry at 60°C for 24 hours. A circular electrode with a diameter of 12 mm was prepared using a punching machine.

[0054] The lithium sheet is used as the counter electrode, the polypropylene microporous membrane is used as the separator, and the electrolyte is 1 mol / L LiPF6 dissolved in ethylene carbonate (EC) + (2) methyl carbonate (DMC) (volume ratio is 1:1). Then, in a vacuum glove box, the battery components including positive and negative battery shells, positive and negative electrode sheets, gaskets, shrapnel, etc. are assembled into button-type half-cells in a specific order.

[0055] The specific assembly process is as follows: first, place the positive electrode shell on the dust-free cloth on the workbench, and place the negative electrode plate in the middle of the positive electrode shell to ensure that there is no contact around it; then press the diaphragm steadily on the surface of the circular plate, and drop about 80uL of electrolyte on the diaphragm to ensure that the diaphragm and the plate are completely soaked; then place the lithium sheet, gasket and shrapnel in sequence, cover the negative electrode shell on it and use a battery sealing machine to seal the battery. After the battery is prepared, it needs to be aged for more than 24 hours before electrochemical testing can be carried out, and the cut-off voltage is 0.01-1.5V.

[0056] The electrochemical performance test results of the silicon oxygen carbon negative electrode materials prepared in Examples 1-7 are shown in Table 1. The test conditions are the same and the current density is 1 A / g.

[0057] Table 1 shows the electrochemical performance test results of the silicon oxygen carbon negative electrode materials prepared in Examples 1-7

[0058]

[0059]

[0060] It can be concluded from Table 1 that the silicon-oxygen-carbon composite negative electrode material prepared in the embodiment of the present invention was assembled into a lithium-ion battery for electrochemical testing. The first discharge capacity reached more than 1500mAh / g, with the highest being 2903mAh / g, the first coulombic efficiency reached 70.59%, and the reversible capacity reached a maximum of 1656mAh / g after 100 charge and discharge cycles, with excellent cycle performance.

[0061] The present invention uses the above-mentioned embodiments to illustrate the detailed process equipment and process flow of the present invention, but the present invention is not limited by the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a silicon-oxygen-carbon negative electrode material, characterized in that: The following steps are involved: (1) Using silicon oxide as a silicon source and anhydrous glucose as a carbon source, a certain amount of silicon oxide is put into a ball mill, and mechanically ball milled with zirconium oxide balls in a certain ratio, so that the particle size of silicon oxide is controlled within a specific range, wherein the ball-to-material ratio of zirconium oxide balls to silicon oxide is (1-10):1; (2) adding a certain ratio of anhydrous glucose and melamine to continue mechanical ball milling so that the carbon source is evenly coated on the surface of the silicon source, then taking out the prepared mixture from the ball mill, and sieving a sample with a suitable particle size with a test sieve, wherein the mass ratio of silicon dioxide, anhydrous glucose and melamine is (1-10): (1-10): 1; (3) placing the mixture within a specific particle size range sieved out in step (2) into a horizontal crucible furnace, and carbonizing it by high-temperature pyrolysis under the protection of an inert gas to remove excess oxygen atoms in the material, thereby obtaining the silicon-oxygen-carbon negative electrode material.

2. The method for preparing the silicon oxygen carbon negative electrode material according to claim 1, characterized in that: In the step (1), the mechanical ball milling time of silicon dioxide and zirconium oxide balls is 1-10 hours, the mechanical ball milling time after adding the mixture of anhydrous glucose and melamine is 1-10 hours, and the mechanical ball milling speed is 100-300 r / min.

3. The method for preparing the silicon oxygen carbon negative electrode material according to claim 1, characterized in that: In the step (1), the particle size of the silicon-oxygen-carbon mixture obtained by mechanical ball milling is 0.05-150 μm.

4. The method for preparing the silicon oxygen carbon negative electrode material according to claim 1, characterized in that: In the step (2), the mesh size of the inspection sieve is 50-500 mesh, and the particle size of the sample sieved out is 0.5-50 um.

5. The method for preparing the silicon oxygen carbon negative electrode material according to claim 1, characterized in that: In the step (3), the heating rate during high-temperature pyrolysis is 0.5-10°C / min, the temperature is heated to 400-1000°C, and the insulation time is 1-15h.

6. The method for preparing the silicon oxygen carbon negative electrode material according to claim 1, characterized in that: In step (3), the inert gas is at least one of helium, nitrogen and argon.

7. The method for preparing the silicon-oxygen-carbon negative electrode material according to any one of claims 1 to 6, wherein the particle size of the silicon-oxygen-carbon negative electrode material is 0.05-50 um.

8. Use of the silicon-oxygen-carbon negative electrode material prepared according to the method for preparing the silicon-oxygen-carbon negative electrode material according to any one of claims 1 to 7 in preparing a lithium-ion battery.